2021
DOI: 10.3390/cancers13020344
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α3β1 Represses Reelin Expression in Breast Cancer Cells to Promote Invasion

Abstract: Integrin α3β1, a cell adhesion receptor for certain laminins, is known to promote breast tumor growth and invasion. Our previous gene microarray study showed that the RELN gene, which encodes the extracellular glycoprotein Reelin, was upregulated in α3β1-deficient (i.e., α3 knockdown) MDA-MB-231 cells. In breast cancer, reduced RELN expression is associated with increased invasion and poor prognosis. In this study we demonstrate that α3β1 represses RELN expression to enhance breast cancer cell invasion. RELN m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
1
14
1
Order By: Relevance
“…Previously, we showed that RNAi-mediated suppression of ITGA3 in MDA-MB-231 cells substantially reduced cell invasion in vitro and metastatic lung colonization in vivo, and we have shown that these phenotypes are due at least partly to the loss of α3β1-dependent gene regulation in these cells [11][12][13]. However, α3β1 also has important roles in cell adhesion and migration, raising the possibility that this integrin also promotes invasion and/or metastasis independently of its ability to regulate gene expression.…”
Section: Plos One α3β1 Promotes Breast Cancer Cell Invasion and Metastatic Colonization Independently Of Global Regulation Of The Transcrmentioning
confidence: 67%
See 3 more Smart Citations
“…Previously, we showed that RNAi-mediated suppression of ITGA3 in MDA-MB-231 cells substantially reduced cell invasion in vitro and metastatic lung colonization in vivo, and we have shown that these phenotypes are due at least partly to the loss of α3β1-dependent gene regulation in these cells [11][12][13]. However, α3β1 also has important roles in cell adhesion and migration, raising the possibility that this integrin also promotes invasion and/or metastasis independently of its ability to regulate gene expression.…”
Section: Plos One α3β1 Promotes Breast Cancer Cell Invasion and Metastatic Colonization Independently Of Global Regulation Of The Transcrmentioning
confidence: 67%
“…To build from our previous investigations of integrin α3β1 in promoting pro-tumorigenic functions of TNBC cells [11][12][13], we used CRISPR to target the ITGA3 gene (which encodes the α3 integrin subunit) within the MDA-MB-231 cell line. As α3 is known to partner exclusively with the β1 integrin subunit [1], this strategy was employed to generate cells in which expression of α3β1 is completely ablated (i.e., α3-Cr cells).…”
Section: Crispr-mediated Ablation Of α3β1 and Rnai-mediated Suppression Of α3β1 Produce Distinct Effects On The Transcriptome Of Mda-mb-2mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a number of studies has reported changes in the expression of reelin in different cancer types even outside the nervous system [37]. Reelin expression has been found reduced in breast [38][39][40], colorectal [41,42], and pancreatic cancers [43], while it has been found to be increased in retinoblastoma [44], myelomas [45], and prostate cancers [39,46,47]. Here, we investigated the expression of reelin in human tissue samples obtained from tumoral lesion and the peritumoral area of GBM.…”
Section: Introductionmentioning
confidence: 99%